Spiritual recovery of people with bipolar disorder in Malaysia - Mohamad Shariff, Nurasikin; Crawford, Paul; Wright, Nicola (2017)
People with any mental disorder can get benefit from the spiritual aspects of life for recovery, particularly in searching for the meaning of life and engaging in meaningful activities. However, little is known about such effects in the population of bipolar disorder. The concepts of spirituality are highly contestable, as they are too broad and removed from the original religious understanding. The concepts are more notable as encompassing multi-dimensional aspects of people’s lives such as social, emotional, and psychological. Viewing that Western or secular worldview dominates most of the literature in spirituality, it is time to explore the concept of spirituality from the Eastern and religious worldview, such as the Malaysian view. Thus, the aim of this study is to provide a conceptual understanding of people with bipolar disorder with a religious affiliation in Malaysia. This study employs a Grounded Theory and explores the narratives from the interviews of 25 participants. The narratives strongly suggest the salient resources or can be referred to as various forms of capital, as in the capital theory, namely, religious, social, psychological, and medicinal. More important is how these capitals are the enablers for recovery in mental health and well-being, where the participants in the sample engage in a more meaningful life and positive adaptations. This study also extends the Bourdieusian spiritual capital, in which the salient resources are termed as the capital bundle. More significant is how the capital bundles are working contiguously in building and accumulating the spiritual capital. This process is conducive to recovery within the social life of people with bipolar disorder or perhaps other mental disorders